2016
DOI: 10.1515/jelf-2016-0019
|View full text |Cite
|
Sign up to set email alerts
|

Teasing in informal contexts in English as an Asian lingua franca

Abstract: This paper explores how speakers of English as a lingua franca (ELF) manage the interactional back-and-forth of teasing, a social action which, being fundamentally ambiguous, is open to interpretation by a target and/or other participants as aggressive in intent. The data reported here draw on the Asian Corpus of English (ACE), and describe some of the more typical teasing practices which occur among Asian ELF speakers in informal, non-task-focused contexts. More specifically, this research explores the interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 35 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…While some studies show evidence of various degrees of difficulty in producing or comprehending humour by language learners as well as different levels of engagement in humour sequences (Davies 2003;Bell 2005), jocular conversations in intercultural settings should be seen as jointly constructed interactional practices (Cheng 2003;Matsumoto 2014). For instance, humour in English as a lingua franca in Asia in the form of teasing, banter or jocular mockery has been found to be frequently used in informal conversations and those attempts at humour tend to be constructed and perceived as jocular (Walkinshaw 2016; see also Matsumoto 2014;Moalla 2015). While studies of casual interactions are very few, institutional interactions have received more attention.…”
Section: Intercultural Studies On Humourmentioning
confidence: 99%
“…While some studies show evidence of various degrees of difficulty in producing or comprehending humour by language learners as well as different levels of engagement in humour sequences (Davies 2003;Bell 2005), jocular conversations in intercultural settings should be seen as jointly constructed interactional practices (Cheng 2003;Matsumoto 2014). For instance, humour in English as a lingua franca in Asia in the form of teasing, banter or jocular mockery has been found to be frequently used in informal conversations and those attempts at humour tend to be constructed and perceived as jocular (Walkinshaw 2016; see also Matsumoto 2014;Moalla 2015). While studies of casual interactions are very few, institutional interactions have received more attention.…”
Section: Intercultural Studies On Humourmentioning
confidence: 99%
“…Habib's (2008) study of humour and disagreement among female ELF users in the US found that humour (particularly jocular teasing) and disagreement were used to maintain and display interactional rapport among interactants (cf. Walkinshaw, 2016;Walkinshaw and Kirkpatrick, 2014). Rogerson-Revell (2007) and Moody (2014) 10.1163/26660393-bja10010 | Contrastive PragmaticS (2020) 1-29 highlight a similar function in business contexts in South East Asia and Japan respectively.…”
Section: 4mentioning
confidence: 99%